KANDUNGAN PROTEIN DAN LEMAK DAGING ITIK KHAKI CAMPBELL FASE STARTER YANG DI BERI PAKAN LARVA MAGOT BLACK SOLDIER FLY - Suparmin Fathan; Muhammad Mukhtar (Gorontalo Journal of Equatorial Animals, 2023)
The purpose of this study was to determine the effect of feeding maggot larvae on the protein and fat content of khaki Campbell duck meat. This study used laying ducks aged 2-8 weeks totaling 100 heads, in each test consisting of 5 heads. The feed given consists of finished feed (BRO1-master), corn, bran, fish meal, maggot larvae, tofu pulp, premixes. The research material used was a complete randomized design (RAL), consisting of 5 treatments and 4 tests. The treatment given was P0= ration without maggot larvae P1 = ration with 3.75 % maggot larvae P2 = ration with 7.5 % maggot larvae P3 = ration with 11.25 % Maggot larvae P4= ration with 15 % maggot larvae. The results showed that the administration of maggot larvae had a noticeable influence on the protein and fat content of Campbell khali duck meat.